Large Planting Stock Type and Mechanical Release Effects on the Establishment Success of Picea glauca Plantations in Quebec, Canada. (15th January 2012) - Thiffault, Nelson; Lafleur, Benoit; Roy, Vincent; DeBlois, Josianne
Abstract : We established four experimental plantations to evaluate the main and interaction effects of timing (year of application) of mechanical release and stock type (containerized or bareroot) on the establishment success of large Picea glauca seedlings eight years after outplanting on high-competition sites in Quebec (Canada). We also monitored percent cover and height of target vegetation groups as well as the amount of photosynthetically active radiation available to crop trees. Our results indicate that the use of large containerized or bareroot stock had limited effects on seedling growth, although bareroot seedlings presented higher mortality than containerized seedlings. Mechanical release enhanced seedling growth, compared to the control. Delaying treatment by two years impacted crop tree dimensions, although differences were minimal. Survival was not affected. We conclude that large containerized seedlings should be favoured over bareroot stock for reforestation on high-competition sites and that the release guidelines developed for standard size seedlings are applicable to the large dimension P. glauca stock tested in this study.